Handling of IPR Violations at the Regional Office of the Ministry of Law and Human Rights of North Sumatra - Lubis, Tiva Novianti; Khalid, Khalid (Law Development Journal, 2023)
Indonesia is the country with the largest population in the world. Of course, there are many cases and violations that occur, one of which is related to intellectual property, where everyone who creates a work certainly has the right to his work if it is registered. However, until now there are still many intellectual property owners who forget or even do not register their work. This is a major factor in the occurrence of intellectual property violations in Indonesia, especially due to the lack of understanding of the importance of registering intellectual property. This is what then attracts the author's attention to be able to examine and learn more about how the handling of IPR violations within the Regional Office of the Ministry of Law and Human Rights of North Sumatra. This research uses normative-empirical research methods using two approaches, namely the statute approach and the case approach. The conclusion obtained is that the law enforcement efforts carried out by the Regional Office of the Ministry of Law and Human Rights of North Sumatra are by conducting cooperation activities in the form of seminars, socialisation, and visits to every region in North Sumatra, in order to provide guarantees of legal certainty for owners of Intellectual Property Rights (IPR) and provide supervision of potential intellectual property violations in each region of North Sumatra.